DINAMIKA KELOMPOK USAHATANI HORTIKULTURA TERHADAP KINERJA PETANI HORTIKULTURA DI DESA WATULIWU KECAMATAN LASUSUA KABUPATEN KOLAKA UTARA - Rismayanti Muh Rusli; Dasmin Sidu; Salahuddin Salahuddin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2022)
This research was motivated by the formation of two horticultural farmer groups in Watuliwu Village in 2019 which experienced many classic problems such as unstable commodity conditions, lack of access to marketing, and the habits of local people who prefer to buy horticultural crops. from outside the area. This study aims to determine the dynamics of farmer groups in horticultural farming, to determine the performance of horticultural farmers, and to determine the relationship between group dynamics and the performance of horticultural farmers in Watuliwu Village, Lasusua District, North Kolaka Regency. This study uses a quantitative descriptive method with proportional random sampling. The results of this study indicate that the dynamics of horticultural farmer groups are classified as dynamic. Meanwhile, the performance of horticultural farmers in Watuliwu Village is quite good, but several indicators still need to be improved. Group dynamics and the performance of horticultural farmers in Watuliwu Village have a very close and significant relationship with a rank correlation coefficient of 0.822 and a significance value of 0.000. So that the better the group dynamics that are formed, the better the performance of horticultural farmers will be.